Redemption rights for acquisition of new emission as a means of corporate management - STETSKO, Mykola (Scientific journal «World of Finance», 2019)
Introduction. There are cause-effect persistent relationships between the quality of corporate management of an enterprise and its ability to attract investments. Among the wide range of issues related to the definition of "corporate management", the least investigated is the means of redemption rights to purchase shares of new emission. The level of protection of investors’ rights depends directly on its capacity, and hence the investment attractiveness of individual enterprises and the capital market of the country.Purpose of the study is to substantiate the recommendations on the practical implementation of the redemption rights of shareholders to purchase shares of new emission.Methods. In order to create the conditions for the practical implementation of the redemption rights, the model of calculating the domestic fair value of redemption rights is substantiated. This model takes into account the following factors: market share price before additional emission, emission rate, emission and cash flows ratio which will be generated by the company owing to the emission results. It is a model for determining the minimum amount of additional cash flow, which should be generated by a company that carries out an additional share emission in order to preserve the market rate that took place before the increaseof the statutory capital, is offered.Results. The work emphasizes that redemption rights (for the purchase of shares) is a means against blurring the value share of individual shareholders, its devaluation and compensation of owners’ losses. The financial aspects of implementation of redemption rights, in particular, their price, fair value and influential factors are analyzed. If the share emission is low, the "blurring" of the market value of the shares in circulation and losses of shareholders will be high. The task of determining the fair value of redemption rights in the article was solved on the basis of comparing the market value of the company to the increase of the statutory capital and potential market capitalization after the additional share emission.Conclusions. It is shown that as a result of implementation of redemption rights, shareholders do not receive real additional income and increase of their assets. To compensate the shareholders losses related to the additional share emission, the necessity to permit the trade of redemption rights and the tax exemption from the sales revenue of these rights is substantiated.